Double Refund Of Engagement Sign On Wedding Cancellation By The Woman Fiqh Munakahat Perspective (Case Study In Tanjung Putus Padang Tualang Village) - Dinda Sri Rezeki (Tunas Institute, 2024)
Engagement is a promise to hold a marriage that is carried out before the marriage contract process occurs. However, in its implementation, problems often arise when the engagement is canceled by one of the parties. One of the practices found was that there was a double return of the sign of engagement for the cancellation of marriage by the woman in Tanjung Putus Village, Padang Tualang. The purpose of this study is to find out the practice of returning double engagement marks for marriage cancellation by women in Tanjung Putus Village and to find out the perspective of munakahat fiqh on the return of double engagement marks by women in Tanjung Putus Village. This study uses a qualitative method with an empirical sociological approach. The results of the study show that in Tanjung Putus Village there is a double return of the engagement sign if the engagement is terminated by the woman, while if the engagement is decided by the man, he does not have the right to ask for back what has been given to the woman. From the perspective of fiqh munakahat, there is no provision that requires the return of the sign of engagement by double the amount. The scholars agree that if the gift at the time of engagement is a dowry, then it must be returned according to the amount given when the engagement bond is canceled. However, scholars differ in their opinion if the gift is in the form of a gift. According to Abu Hanifah and Malikiyah scholars, it is permissible to ask for the gift that has been given if the item is still intact, while Shafi'iyah and Hanabillah are of the opinion that the gift that has been given should not be asked for again. However, there are no scholars who allow the return of double the sign of engagement, either in the form of dowry or gifts.